Asuhan Kebidanan Kehamilan Trisemester III pada Ny.S Usia 27 Tahun G2P1A0H1 Dengan Animia Sedang dan Obesita DI UPT PUSKESMAS Sesela Kabupaten Lombok Barat - sesele, jarsiah; Setyawati, Lina; Aryatini, Lia; Fitriani, Dewi; Hardiyanti, Wiwin (STIKES Yarsi Mataram, 2024)
In obese pregnant women with a history of abortion, it is a high-risk pregnancy that requires special attention, obesity with a history of abortion can endanger the condition of the mother and baby. A history of abortion in pregnancy has an effect on the next pregnancy, both the initial complications and the outcome of the pregnancy itself, there can be bleeding/recurrent abortion, premature delivery, risk of LBW, postpartum infection method (containing the method, place, and time of the study), anemia can have a negative impact on maternal and infant morbidity and mortality. The impact of anemia on the fetus includes intra uterine growth retardation (IUGR), premature babies, babies with congenital defects, low birth weight (LBW) and an increased risk of fetal death in the womb. The goal is to maintain midwifery pregnancy TM III in Mrs. S, 27 years old G2P1A0H1 with moderate anemia and obesity at the Sesela Health Center UPT, West Lombok Regency. The results of this midwifery care provide IEC to pregnant women about midwifery care with moderate anemia and obesity. In conclusion, anemia is a condition characterized by reduced hemoglobin in the body. Hemoglobin is a metalloprotein, a protein containing iron in red blood cells that functions as a carrier of oxygen from the lungs to the entire body. Iron deficiency anemia is anemia caused by a lack of iron used for the synthesis of hemoglobin (Hb). Normal Hb in pregnant women >11 g/dl. The conclusion is able to carry out midwifery care for obese and anemic pregnant women.